Women's Choices in Europe Influence of Gender on Education, Occupational Career and Family Development - Quaiser-Pohl, Claudia; Endepohls-Ulpe, Martina (Waxmann Verlag, 2012)
The options women have to shape their lives have dramatically increased in the last decades, and this is true for all European countries. Changes in their societies with respect to women's rights have been fundamental, amongst other things as a result of the women's movement, which caused one of the greatest social revolutions of the 20th century. But considering the different starting points of the women's movement and all the other historical, cultural and political differences in the European nations it is no surprise that the situation of women is different, too, and that the process of reaching equal status with men has come to different stages in different areas of life. And, of course, there are still some fields of remarkable gender inequalities which can be noticed all over Europe. This book wants to give some insight into the differences as well as the similarities of women's lives, their educational and occupational attainment and their choices with respect to occupational career and family life in several European countries. The authors come from different countries and represent different disciplines. Therefore the chapters cover a large variety of scientific approaches and draw a fine-grained picture of the situation of women´s lives in Europe.